Rued Langgaard — A Symbolistic Composer? - Frank, Tine (Danish Yearbook of Musicology, 1996)
Rued Langgaard – A Symbolistic Composer? The Danish composer and organist Rued Langgaard (1893-1952) fits in neither with the prevailing musical trends in Denmark nor with his contemporaries nor with the values of his time. He can, however, be seen as a late representative of the symbolistic movement in Denmark which arose in the 1890s. This article is an introduction to the symbolistic elements in Langgaard’s productions. After a short definition of symbolism, Langgaard is compared to the symbolistic poets — in philosophy and in use of symbols — and some of his work’s outstanding features are pointed out. Other characteristics of Langgaard’s music are mentioned. Finally, the term „symbolism“, as applied to music and to Langgaard in particular, is discussed.